2018
DOI: 10.26226/morressier.5af060621dd164001d5ef330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

01 / the Prevalence and Risk Factors of Mycoplasma Genitalium Infection Among Infertile Women in Ibadan, Oyo State, Nigeria: A Cross-Sectional Study.

Abstract: A cross-sectional study involving 2 hospitals, 402 women (267 infertile and 135 fertile) were enrolled between March and November 2015, using random, systematic sampling technique. Information was obtained, using structured questionnaire, on sociodemographic and behavioral characteristics of the respondents and endocervical swabs were obtained for DNA extraction. The presence of Mycoplasma genitalium Mgpa gene was detected from the extracted DNA by the use of conventional PCR. Bands corresponding to 495kb were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This implies that a unit increase in the training in rice farming or production will increase the potential capacity to produce rice seed by 1.3327 as shown in Table 4. This finding is in agreement with the study of Ajani (2000) who observed that training experience enhance farm productivity and efficiency in his study of resources productivity in food crop farming in Northern area of Oyo State Nigeria. Formal training in rice seed production: As revealed in this study (Table 4), training in rice seed production had a negative and significant with the potential capacity for rice seed production at 1% significance level in the study area.…”
Section: Determinants Of Rice Farming Households' Potential Capacity ...supporting
confidence: 92%
“…This implies that a unit increase in the training in rice farming or production will increase the potential capacity to produce rice seed by 1.3327 as shown in Table 4. This finding is in agreement with the study of Ajani (2000) who observed that training experience enhance farm productivity and efficiency in his study of resources productivity in food crop farming in Northern area of Oyo State Nigeria. Formal training in rice seed production: As revealed in this study (Table 4), training in rice seed production had a negative and significant with the potential capacity for rice seed production at 1% significance level in the study area.…”
Section: Determinants Of Rice Farming Households' Potential Capacity ...supporting
confidence: 92%
“…A number of previous research studies in relation to writings on vehicles have been carried out, each applying a different approach – stylistic, linguistic or ethnographic – to examine their meanings (see Ajani, 1999; Asangba and Agoswin, 2015; Chiluwa, 2008; Jordan, 1978; Mgbemena, 2013; Nwagbara, 2008; Oduro-Frimpong, 2013). However, the scholars who have carried out extensive research into the communicative power of writings on vehicles hold divergent views as to the influence of sociocultural factors such as age, sex, status, ethnicity and religion on the messages written.…”
Section: Previous Studiesmentioning
confidence: 99%